Low-energy-ion accelerators for biological applications and research - L. D. Yu (2018)
Ion beams have been developed an important application in biology, life science and medical science for long time, but they have been in the high energy regime (normally > 102 MeV). Recently the application has been expanded to the low energy regime (< MeV, and particularly ≤ the order of 10 keV). At Chiang Mai University, Thailand, we have developed and applied specially designed low-energy-ion accelerators to serve for agricultural product development and biological fundamental research. Ion beams at energy of an order of 10 keV have been applied to induce mutations of local crops such as rice, flowers and vegetables to increase the qualities and to induce gene transfer in biological cells to control plant diseases. Ions with energy of an order of keV have been applied to investigate ionized particle irradiation effect on DNA and cell envelopes for understanding fundamentals in ion interaction with the biological organisms. Ion beams at energy of MeV have been applied to analyze biological samples for mineral contents and elemental distribution measurements. Our activities have demonstrated high applicability of low-energy-ion accelerators which are reasonably and economically available for developing countries to develop their research and useful applications in novel areas.